Freiburg Personality Inventory for assessment of the police officers - Omelyanovich, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Background. Psychological and psychiatric work activity support of law enforcement officers is a basic component for the efficient functioning of the internal affairs institutions. Improvement of this work is impossible without increasing the effectiveness of the personnel psychological selection. Methods. Research methods included "Freiburg Personality Inventory" (FPI) - Option «B» and «Minnesota Multiphasic Personality Inventory» – MMPI. The study group comprised of 158 respondents: 79,1 % (n=125) were men and 20,9% (n=33) - women. To analyze the results obtained, we used the methods of descriptive statistics, frequency analysis, and Kendell rank correlation. Results. Particular attention should be paid to the fact, that it would be logical to expect the presence of correlations between FPI and MMPI scales, similar in their diagnostic orientation. But such correlations were found neither for the male or female gender (τ-b ≤0,17;p ≥0,06). This unexpected discovery, as well as the lack of systematic and gender-wide universality between the FPI and MMPI scores, are pointing to a rather serious content heterogeneity between these psychological tests. Conclusion. The results of the analysis do not provide an opportunity to recommend the wide usage of FPI questionnaire in practical activities for the professional selection of law enforcement officers.